The effect of intended duration of clopidogrel use on early and late mortality and major adverse cardiac events in patients with drug-eluting stents - Butler, M.; Eccleston, D.; Clark, D.; Ajani, A.; Andrianopoulos, N.; Brennan, A.; New, G.; Black, A.; Szto, G.; Reid, Christopher; Yan, B.; Shaw, J.; et al. (Mosby, INC, 2009)
Background: The optimal duration of clopidogrel use for prevention of stent thrombosis with drug-eluting stent (DES) use is uncertain. Our objective was to determine whether the planned duration of clopidogrel at the time of percutaneous coronary intervention affected patient outcomes. Methods: We analyzed data from 2,980 patients who underwent percutaneous coronary intervention in the Melbourne Interventional Group registry who had 12-month follow-up. We compared outcomes at 30 days and 12 months according to planned duration of clopidogrel use. Results: Twelve-month mortality was significantly lower in patients with a DES with a longer (=12 months) planned duration of clopidogrel when compared with a shorter (=6 months) planned duration (2.8% vs 5.3%, P = .012). However, myocardial infarction, target-vessel revascularization, and overall major adverse cardiac events were similar in the longer- and shorter-duration clopidogrel strategies. In contrast, in patients receiving a bare-metal stent, mortality at 12 months was similar among the clopidogrel-duration strategies. Kaplan-Meier analysis demonstrated improved cumulative survival with planned clopidogrel use of =12 months (log rank P = .017), and the propensity score-adjusted odds ratio was 0.59 (95% confidence interval 0.35-0.99, P = .04). Premature cessation of clopidogrel in DES patients was documented in 5.2% of patients alive at 30-day follow-up, and these patients had increased 12-month mortality (10.6% vs 1.4%, P < .0001) and major adverse cardiac events (22.4% vs 12.0%, P = .005). Conclusions: These data suggest that in patients treated with DES, longer (=12 months) planned duration of clopidogrel results in reduced 12-month mortality and that premature cessation of clopidogrel results in significantly higher event rates. Randomized studies are urgently needed to address this issue. © 2009 Mosby, Inc.